Preparation method of CuInSe2 thermoelectric material
By using high-purity raw materials and optimized sintering processes, combined with high-temperature vacuum sintering and hot pressing, high-density CuInSe2 materials were prepared, solving the problems of complex preparation methods and high costs in existing technologies. This achieved high performance and stability of the materials, promoting their industrial application.
Patent Information
- Application Number
- CN202511393972.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-01-06
AI Technical Summary
Existing methods for preparing CuInSe2 materials are complex and costly, and the thermoelectric figure of merit (ZT value) of these materials is generally low, making it difficult to meet the requirements of practical applications.
By employing high-purity elemental raw materials, precise stoichiometry, and a double quartz tube vacuum sealing design, combined with high-temperature sintering and hot-pressing sintering processes, and through optimized heating, holding, and cooling rates, high-density CuInSe2 bulk materials were prepared.
A CuInSe2 material with pure phase and good crystallinity was obtained, exhibiting excellent mechanical properties and significantly improved thermoelectric properties, and has good market application prospects.
Smart Images

Figure CN121269640A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermoelectric materials technology, and in particular to a method for preparing CuInSe2 thermoelectric material. Background Technology
[0002] Thermoelectric materials are functional materials capable of directly converting heat energy into electrical energy, and they have significant application value in fields such as space exploration power supplies, industrial waste heat power generation, and localized precision refrigeration. Compared with traditional power generation and refrigeration technologies, thermoelectric conversion technology has significant advantages such as no moving parts, no working medium, quiet operation, high reliability, and long lifespan. Against the backdrop of global efforts to improve energy efficiency and develop green and sustainable energy technologies, utilizing thermoelectric materials to recover the vast waste heat resources generated by automobile exhaust and industrial kilns has become a highly promising technological solution.
[0003] CuInSe2, an important semiconductor material among group I-III-VI2 chalcopyrite compounds, is considered a promising medium-to-high temperature thermoelectric material due to its high Seebeck coefficient and excellent electrical transport properties. Furthermore, its constituent elements are environmentally friendly, free of highly toxic elements such as lead and cadmium, meeting green environmental protection requirements. However, unoptimized CuInSe2 has a high intrinsic lattice thermal conductivity, resulting in a generally low thermoelectric figure of merit (ZT value), making it difficult to meet the conversion efficiency requirements of practical applications. This inherent drawback severely limits the commercial application of this material.
[0004] Currently, there are various methods for preparing CuInSe2 materials, including melting, solvothermal, sputtering, vacuum evaporation, and solid-state reaction sintering. However, these methods generally have some limitations: for example, melting easily introduces impurity phases and consumes a lot of energy; while solvothermal methods can produce nanoparticles, subsequent densification is difficult; and vacuum evaporation and sputtering are expensive, complex, and have low yields, making large-scale production difficult. Although solid-state reaction methods are relatively simple, traditional sintering processes often suffer from incomplete reactions, component segregation, and low product density, affecting the consistency and reproducibility of the material's thermoelectric properties.
[0005] Therefore, developing a simple, low-cost, easily scalable synthesis method for producing high-performance, highly stable CuInSe2 bulk materials is of great significance for promoting the practical application of this type of thermoelectric material. Summary of the Invention
[0006] The purpose of this invention is to address the problems of complex processes and high costs in the current preparation methods of CuInSe2 materials, and to propose a method for preparing CuInSe2 thermoelectric materials.
[0007] The technical solution of the present invention: a method for preparing CuInSe2 thermoelectric material, comprising the following steps:
[0008] Step A: Weigh and mix Cu, In, and Se in a molar ratio of 1:1:2 and load the mixture into the first quartz tube;
[0009] Step B: Place the first quartz tube into the second quartz tube, evacuate the vacuum, and seal the tube;
[0010] Step C: Place the sealed second quartz tube in a tube furnace for high-temperature sintering to obtain CuInSe2 material.
[0011] Optionally, in step B, the vacuum level of the vacuum pump is 10. -5 ~10 -6 Torr.
[0012] Optionally, the high-temperature sintering in step C includes the following stages:
[0013] During the heating phase, the temperature is increased from room temperature to 800℃ at a rate of 4–5℃ / min;
[0014] The insulation stage involves maintaining the temperature at 800℃ for 55-65 hours.
[0015] During the cooling phase, the temperature was reduced from 800°C to room temperature at a rate of 10–15°C / min.
[0016] Optionally, the diameter of the first quartz tube is 8-12 mm, and the diameter of the second quartz tube is 10-14 mm.
[0017] Optionally, after step C, the following may also be included:
[0018] Step D: Grind the sintered product into powder;
[0019] Step E: The powder is hot-pressed for 30 minutes under a pressure of 50 MPa, a temperature of 773 K, and a vacuum environment below 8 Pa to obtain a high-density CuInSe2 bulk material.
[0020] Optionally, the purity of the Cu, In, and Se elements is not less than 99%.
[0021] Compared with the prior art, this application includes at least one of the following beneficial technical effects:
[0022] By employing high-purity elemental raw materials, precise stoichiometry, and a double quartz tube vacuum sealing design, the loss of volatile component selenium and external contamination at high temperatures were effectively prevented, ensuring the full progress of the synthesis reaction and ultimately obtaining CuInSe2 material with pure phase and good crystallinity.
[0023] Polycrystalline materials prepared by traditional methods often suffer from high porosity and poor density. This invention achieves rapid densification of powder under high temperature and pressure through a key post-processing step of hot pressing sintering. The resulting bulk material has high density and tight grain boundary bonding, thus possessing superior mechanical strength and toughness, meeting the mechanical reliability requirements of thermoelectric device processing and service.
[0024] This invention promotes the full diffusion and orderly arrangement of atoms through an optimized sintering process. Combined with the high density and good electrical contact brought about by the hot pressing process, the electrical transport performance of the material is optimized. At the same time, the scattering effect of phonons by grain boundaries is enhanced, which helps to reduce the lattice thermal conductivity. Ultimately, the thermoelectric performance of the material is significantly improved.
[0025] In summary, the method for preparing CuInSe2 thermoelectric material provided by this invention is not only stable, easy to operate, and highly reproducible, but also successfully produces a bulk material with high purity, high density, excellent mechanical properties, and superior thermoelectric properties. It overcomes many shortcomings of the prior art and has significant practical significance for production and good market application prospects. Attached Figure Description
[0026] Figure 1 The XRD patterns of the samples obtained in Examples 1-5;
[0027] Figure 2-a This is a crystallographic image of the single-crystal sample obtained in Example 2;
[0028] Figure 2-b The crystal structure diagram obtained in Example 2 is shown.
[0029] Figure 2-c The image shows the crystal obtained in Example 2;
[0030] Figure 3 The figures shown are TG-DSC curves of the hot-pressed samples obtained in Examples 1-5, with insets showing photographs of the hot-pressed samples before and after the TG-DSC test.
[0031] Figure 4 The elastic modulus diagram of the sample obtained in Example 4;
[0032] Figure 5 The conductivity diagram of the sample obtained in Example 5 is shown in the inset, which is a photograph of the test sample.
[0033] Figure 6 Seebeck coefficient of the sample obtained in Example 5;
[0034] Figure 7 The total thermal conductivity of the sample obtained in Example 5;
[0035] Figure 8 The thermoelectric figure of merit of the sample obtained in Example 5;
[0036] Figure 9 The powder XRD patterns of the sample before and after the thermal conductivity performance test are obtained in Example 5. Detailed Implementation
[0037] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features described therein can be combined with each other.
[0038] Example 1: A method for preparing a CuInSe2 thermoelectric material consists of the following steps:
[0039] Raw material preparation: Select copper powder (Cu), indium powder (In), and selenium powder (Se) with a purity of not less than 99% as starting materials. Accurately weigh each elemental powder according to the stoichiometric molar ratio of Cu:In:Se = 1:1:2.
[0040] Tubing: The uniformly mixed raw material powder is loaded into a first quartz tube with a diameter of 10 mm. Then, this first quartz tube is carefully placed into a second quartz tube with a larger diameter (12 mm), forming a double-tube structure.
[0041] Vacuuming and tube sealing: Connect the above-mentioned double-tube structure to a high-vacuum system for vacuuming until the system vacuum level reaches 5.0 × 10⁻⁶. -6 Torr, followed by rapid sealing using an oxyhydrogen flame to ensure the quartz tube is completely sealed.
[0042] Solid-state sintering: The sealed quartz tube is placed horizontally in the constant-temperature zone of a tube furnace for a high-temperature solid-state reaction. The sintering procedure is as follows:
[0043] Heating phase: The temperature is increased from room temperature to 800℃ at a rate of 4.5℃ / min;
[0044] Insulation stage: Maintain constant temperature at 800℃ for 60 hours;
[0045] Cooling stage: Cool along with the furnace, controlling the cooling rate at approximately 12℃ / min until it reaches room temperature.
[0046] Grinding: Take out the product after the reaction and grind it into a uniform fine powder by hand in an agate mortar.
[0047] Hot pressing sintering: The ground powder is loaded into a graphite mold with an inner diameter of 10 mm. The powder is wrapped with carbon paper on both sides and a graphite rod is used as a press head. The mold is then transferred to a hot pressing sintering furnace and held under axial pressure of 50 MPa, temperature of 773 K (about 500 °C), and vacuum environment of less than 8 Pa for 30 minutes to finally obtain a dense CuInSe2 bulk material.
[0048] Example 2: The preparation steps of this example are basically the same as those of Example 1, the only difference being the holding time in the solid-state sintering step 4;
[0049] The heating rate at 4.5°C / min to 800°C during the heating phase and the cooling rate at 12°C / min to room temperature during the cooling phase were consistent with those in Example 1; however, the holding time was extended from 60 hours to 500 hours.
[0050] like Figure 2-a , Figure 2-b , Figure 2-c As shown, CuInSe2 crystallizes in space group I42d (No. 122), where both Cu and In atoms are tetracoordinated, forming tetrahedra.
[0051] Example 3: This example repeats the preparation process of Example 1. All steps and parameters (including raw material ratio, vacuum degree, sintering regime, and hot pressing conditions) are exactly the same as in Example 1. This example is used to verify the repeatability and stability of the preparation method described in this invention. Multiple repeated experiments successfully synthesized CuInSe2 materials with pure phases and consistent microstructures, proving that the process has good reproducibility and is suitable for large-scale preparation.
[0052] Example 4: Based on Example 1, this example tested the mechanical properties of the hot-pressed sintered bulk material.
[0053] The preparation process is exactly the same as in Example 1.
[0054] The obtained high-density CuInSe2 bulk material was processed into standard-sized test strips, and its elastic modulus and hardness were determined using a nanoindenter or a universal testing machine.
[0055] Test results are as follows Figure 4 The results show that the CuInSe2 material prepared by this method possesses good mechanical strength and toughness, meeting the mechanical property requirements of thermoelectric devices during fabrication and service. Figure 4 It can be seen that CuInSe2 has a low average sound velocity and a high Green's constant, corresponding to strong lattice anharmonicity.
[0056] Example 5: The thermoelectric properties of the material prepared according to the method of Example 1 were comprehensively evaluated.
[0057] The preparation process is exactly the same as in Example 1.
[0058] The hot-pressed bulk material is cut and polished into samples of specific shapes, which are then used for measurement:
[0059] conductivity such as Figure 5 As shown: Measurements were taken at different temperatures using the four-probe method. Figure 5 It is known that CuInSe2 has low conductivity, and its conductivity is expected to be further improved.
[0060] Seebeck coefficient as Figure 6 As shown: Calculated by measuring the thermoelectric potential, from... Figure 6 It can be seen that the prepared CuInSe2 is an n-type semiconductor with a large absolute value of Seebeck coefficient, which is beneficial for the regulation of electrical transport.
[0061] Thermal conductivity such as Figure 7 As shown: The thermal diffusivity is measured using the laser scintillation method and calculated using specific heat capacity and density. Figure 7 It is known that CuInSe2 has a low total thermal conductivity, ranging from 3.5 to 1.0 W / m / K, and it is expected that its total thermal conductivity can be further reduced.
[0062] Finally, according to the formula ZT=(S 2 The thermoelectric figure of merit ZT of the material is calculated by σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the total thermal conductivity, and T is the absolute temperature; Figure 8 It can be seen that the prepared CuInSe2 ZT max It is approximately 0.12, and it has potential thermoelectric properties.
[0063] It should be noted that, as Figure 1 The XRD patterns of the samples obtained in Examples 1-5 were used to synthesize a pure phase CuInSe2 sample through solid-state synthesis; Figure 3 The TG-DSC curves are the thermal analysis results of the samples obtained in Examples 1-5 after hot pressing; inset: photographs of the hot-pressed samples before and after TG-DSC testing; from Figure 3 It can be seen that CuInSe2 maintains thermal stability below 400℃;
[0064] Performance test results show that the CuInSe2 material prepared by this invention exhibits excellent and stable thermoelectric properties over a wide temperature range. Figure 9 The XRD patterns show that the phase of the material did not change after the performance test, which proves its good thermal stability. The hot-pressed CuInSe2 sample has good stability.
[0065] It is worth noting that this invention, by employing high-purity elemental raw materials, precise stoichiometry, and a double-quartz tube vacuum sealing design, effectively prevents the loss of the volatile component selenium and external contamination at high temperatures, ensuring the full progress of the synthesis reaction and ultimately obtaining a CuInSe2 material with pure phase and good crystallinity. Polycrystalline materials prepared by traditional methods often suffer from high porosity and poor density. This invention, through the key post-processing step of hot-pressing sintering, achieves rapid densification of the powder under high temperature and pressure. The resulting bulk material has high density and tight grain boundary bonding, thus possessing superior mechanical strength and toughness, meeting the requirements for material mechanical reliability in the processing and service of thermoelectric devices.
[0066] This invention promotes the full diffusion and ordered arrangement of atoms through an optimized sintering process (such as precisely controlled heating / cooling rates and sufficient holding time). Combined with the high density and good electrical contact brought about by hot pressing, this optimizes the material's electrical transport properties (such as conductivity and Seebeck coefficient). Simultaneously, the enhanced phonon scattering effect of grain boundaries helps reduce lattice thermal conductivity, ultimately resulting in a significant improvement in the material's thermoelectric figure of merit (ZT value). The entire process requires no complex and expensive equipment, has high raw material utilization, a relatively short cycle time, and is easy to scale up and control process parameters. It provides a reliable technical path for the large-scale, low-cost preparation of high-performance CuInSe2 thermoelectric materials, strongly promoting their industrial application. The CuInSe2 thermoelectric material and its preparation method provided by this invention are not only stable, easy to operate, and highly reproducible, but also successfully prepare bulk materials with high purity, high density, excellent mechanical properties, and superior thermoelectric properties. This overcomes many shortcomings of existing technologies and has significant practical production implications and promising market application prospects.
[0067] The above specific embodiments are merely several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant teachings of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.
Claims
1. A method for preparing a CuInSe2 thermoelectric material, characterized in that, Includes the following steps: Step A: Weigh and mix Cu, In, and Se in a molar ratio of 1:1:2 and load the mixture into the first quartz tube; Step B: Place the first quartz tube into the second quartz tube, evacuate the vacuum, and seal the tube; Step C: Place the sealed second quartz tube in a tube furnace for high-temperature sintering to obtain CuInSe2 material.
2. The method for preparing a CuInSe2 thermoelectric material according to claim 1, characterized in that, In step B, the vacuum level is 10. -5 ~10 -6 Torr.
3. The method for preparing a CuInSe2 thermoelectric material according to claim 1, characterized in that, The high-temperature sintering in step C includes the following stages: During the heating phase, the temperature is increased from room temperature to 800℃ at a rate of 4–5℃ / min; The insulation stage involves maintaining the temperature at 800℃ for 55-65 hours. During the cooling phase, the temperature was reduced from 800°C to room temperature at a rate of 10–15°C / min.
4. The method for preparing a CuInSe2 thermoelectric material according to claim 1, characterized in that, The diameter of the first quartz tube is 8-12 mm, and the diameter of the second quartz tube is 10-14 mm.
5. The method for preparing a CuInSe2 thermoelectric material according to claim 1, characterized in that, Step C is followed by: Step D: Grind the sintered product into powder; Step E: The powder is hot-pressed for 30 minutes under a pressure of 50 MPa, a temperature of 773 K, and a vacuum environment below 8 Pa to obtain a high-density CuInSe2 bulk material.
6. The method for preparing a CuInSe2 thermoelectric material according to claim 1, characterized in that, The purity of Cu, In, and Se is not less than 99%.